Wpływ renty położenia na atrakcyjność inwestycyjną lokalizacji na terenie dużego miasta w świetle wybranych teorii - Zakrzewska-Półtorak, Alicja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The boundaries of big cities are expanded overcoming successive development thresholds. They acquire rural areas what is an answer to the rising demand for building areas. If the thresholds are relatively easy to overcome (using accessible technologies and techniques) a city or an agglomeration is more attractive to potential investors. The main motives that attract investors (among others foreign investors) to site their ventures in big cities are so called economies of agglomeration: positive knowledge spillovers, access to thick specialist factor market and having close relationships with suppliers and clients etc. and demonstration effects of competitors' and cooperators' behaviour. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 271-280